The role of SWOT analysis in evaluating performance and developing the strategic plan for the non-profit sector - Mabrouk, Atef Mohammad Abd El-Bari; Taha, Mohammad Al-Mahdi Mustafa (Journal of Economic, Administrative and Legal Sciences, 2021)
The study aimed to shed light on the concepts of internal and external environmental analysis among Non-profit associations in Riyadh and determination of impact of environmental analysis variables on performance assessment requirements, and the strategic planning mechanism in these associations accordingly. The importance of the study stems from supporting officials in the practice of strategic planning, which helps organizations achieve their goals, and the application to a non-profit sector is characterized by being more sensitive to the needs of the masses and societies, in addition to what the study adds to the Arab library interested in strategic planning. The formulation of the main hypothesis was “There is a significant relationship between the environmental analysis variables and the performance evaluation requirements of Non-profit associations”. The questionnaire was developed to collect data, and the number of responses reached 391 employees of the applied societies. The most important results of the study include, among other things: The variables value of internal and external environmental analysis, and that of the variables of effectiveness, efficiency, suitability and performance continuity are both above medium; There is a significant impact of the variables of internal and external environmental analysis on both the effectiveness of the performance, and the adequacy of the performance for beneficiary's objectives; There is a significant effect of the external environmental analysis variables on the efficiency of performance and on the continuity of the performance of the associations, while there is no significant effect of the variables of internal environmental analysis.
Keywords: environmental analysis; Performance evaluation; Non-profit associations